2016
DOI: 10.1111/jfd.12509
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus garvieae outbreaks in Brazilian farms Lactococcosis in Pseudoplatystoma sp. – development of an autogenous vaccine as a control strategy

Abstract: This study evaluated the control of streptococcosis outbreaks in Brazil, isolated from diseased sorubim and identified as Lactococcus garvieae by genetic sequencing. This report determined the potential for lactococcosis control in sorubim Pseudoplatystoma sp. with two vaccines: an aqueous-based, whole-cell inactivated vaccine (bacterin) and an oil-adjuvanted bacterin. Their efficacy was evaluated at 30 days post-vaccination (d.p.v.) by challenge with L. garvieae, and the antibody production response at 15, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Among the immunological tests, the most frequent ones are: complete hematological analysis by counting erythrocytes; thrombocytes and leukocytes; differential white cell count; hematocrit; glucose; organ histology, and immunological essays such as serology, specific antibody titration, and agglutination [4,29,57]. Furthermore, toxicity tests can be also conducted using zebrafish such as embryotoxicity, hepatotoxicity, neurotoxicity, endocrine toxicity, genotoxicity, among others as proposed by Bailone et al [3].…”
Section: Zebrafish Model and Vaccines Testing Vaccination Safetymentioning
confidence: 99%
“…Among the immunological tests, the most frequent ones are: complete hematological analysis by counting erythrocytes; thrombocytes and leukocytes; differential white cell count; hematocrit; glucose; organ histology, and immunological essays such as serology, specific antibody titration, and agglutination [4,29,57]. Furthermore, toxicity tests can be also conducted using zebrafish such as embryotoxicity, hepatotoxicity, neurotoxicity, endocrine toxicity, genotoxicity, among others as proposed by Bailone et al [3].…”
Section: Zebrafish Model and Vaccines Testing Vaccination Safetymentioning
confidence: 99%
“…Neither clinical signs nor mortalities were observed in fish from the control groups during the experimental period. The study of Fukushima et al [6] represented the first record, from Brazil, of L.garvieae infection in commercial farms cultivating tropical catfish barred sorubim and hybrid sorubim. This pathogen is a classical etiologic agent, responsible for diseases in cold-water fish [3].…”
Section: Diagnostic-isolation and Identification Of Lactococcus Garvieaementioning
confidence: 99%
“…Fukushima et al [6] concluded that administration of the oiladjuvanted vaccine increased the level of specific antibodies and improved the agglutination ability and survival probability of sorubim exposed to live L. garvieae. These results also demonstrated that the oil-adjuvanted vaccine enhanced the potency and duration of protection against L. garvieae infection and, in the future, could offer an appropriate strategy to prevent these infections in Brazilian sorubim farms.…”
Section: Control Strategiesmentioning
confidence: 99%
See 2 more Smart Citations